A Concept of Beauty as Overt and Covert Culture in American Fashion Movies: A Semiotic Analysis on The Devil Wears Prada, Sex and The City I, and Sex and The City II - , Ishmiyatillah; , Dr. Ida Rochani Adi, S.U. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This thesis aims to study the images of womenâs ideal beauty as the forms of overt and covert culture in American fashion movies. The study is performed based on these formulated problems: 1) How women regarding their appearance are represented in American fashion movies? 'and 3) How do the movies perceive womenâs role in society related to the myth?. The object of study is three box office fashion movies in the US: The Devil Wears Prada, Sex and the City I, and Sex and the City II. The theoretical framework applied in the study is that beauty myth is the ideology of beauty that is made pervasive in American mass culture through the images of womenâs ideal beauty in American mediaâin this case, fashion movies. The movies are examined using Barthesâ semiological approach in which any materials of speech or communication in media (pictures, written and spoken words) are regarded as signifying certain concept or idea. The results of the analysis lead to the findings that as a media of American popular culture The Devil Wears Prada, Sex and the City I, and Sex and the City IIâs attitude towards beauty myth is supportive. Overtly, the movies show and tell that general standard of ideal beauty in American mass media (white, thin, flawless skin, ageless look, well-groomed and fashionable), labeled fashion products and lavish lifestyle in beauty maintenance and fashion are preferable and pleasurable